Cost-effectiveness of pembrolizumab in combination with chemotherapy versus chemotherapy and pembrolizumab monotherapy in the first-line treatment of squamous non-small-cell lung cancer in the US. (3rd July 2019) - Insinga, Ralph P.; Vanness, David J.; Feliciano, Josephine L.; Vandormael, Kristel; Traore, Sory; Ejzykowicz, Flavia; Burke, Thomas
Abstract: Objective: To describe the cost-effectiveness of pembrolizumab plus chemotherapy (carboplatin and paclitaxel or nab-paclitaxel; P + C) in metastatic, squamous, non-small-cell lung cancer (NSCLC) patients in the US. Methods: A model comparing P + C versus C alone is developed utilizing partitioned survival analysis. Primary clinical efficacy, treatment utilization, health utility and safety data are derived from the KEYNOTE-407 trial and projected over 20 years. Costs for drugs and non-drug disease management are also incorporated. Additionally, the cost-effectiveness of P + C vs. pembrolizumab monotherapy (P) is evaluated via an indirect treatment comparison, for patient subgroups with PD-L1 Tumor Proportion Score (TPS) ≥ 50% and 1–49%. Results: Overall, P + C is projected to increase life expectancy by 1.95 years vs. C (3.86 versus 1.91). The resultant ICER is $86, 293/QALY. In patients with PD-L1 ≥ 50%, 1–49% and <1 the corresponding incremental cost-effectiveness ratios (ICERs) are $99, 777/QALY, $85, 986/QALY and $87, 507/QALY, respectively. Versus P, in the PD-L1 ≥ 50% subgroup, P + C appears cost saving; however, this result should be interpreted with caution as there is considerable uncertainty in the relative efficacy of these comparators. Conclusions: Across all eligible patients, the addition of pembrolizumab to chemotherapy is projected to approximately double life expectancy, yielding an extension to a point not previously seen in metastatic squamous NSCLC. Overall, and within all relevant PD-L1 subgroups, use of P + C yields an ICER below $100, 000/QALY, and can be a cost-effective first-line treatment for eligible metastatic squamous NSCLC patients for whom chemotherapy is currently administered. In the PD-L1 ≥ 50% subgroup, additional follow-up within trials of pembrolizumab plus chemotherapy and pembrolizumab monotherapy are needed to better define cost-effectiveness between these comparators.